THE ROLE OF BRAND AWARENESS IN MEDIATING THE EFFECT OF VIRAL MARKETING ON PURCHASE DECISIONS (A Study on Consumers of Tukies Coconut Products in Gianyar Regency) - Ida Ayu Made Citra Swandewi; Tjokorda Gde Raka Sukawati; Putu Saroyini Piartrini; Agoes Ganesha Rahyuda (Adisam Publisher, 2025)
The rapid development of the digital era has driven substantial transformations in marketing practices. Many businesses now compete to design creative and interactive marketing strategies. Amid increasingly intense competition, Tukies Coconut an ice cream brand has implemented viral marketing strategies by utilizing social media platforms to enhance consumer engagement and expand market reach. This study aims to explain the mediating role of brand awareness in the influence of viral marketing on purchase decisions. The research was conducted in Gianyar Regency with a sample of 110 respondents selected using purposive sampling. Data were collected through questionnaires and analyzed using path analysis with SPSS 25.0. The findings reveal that viral marketing has a positive and significant effect on purchase decisions. Viral marketing also has a positive and significant effect on brand awareness. Furthermore, brand awareness significantly influences purchase decisions and is able to mediate the relationship between viral marketing and purchase decisions.